Population pharmacokinetics of exogenous biotin and the relationship between biotin serum levels and in vitro immunoassay interference. (November 2017) - Grimsey, Paul; Frey, Nicolas; Bendig, Garnet; Zitzler, Juergen; Lorenz, Oliver; Kasapic, Dusanka; Zaugg, Christian E
Aim: Biotin in human serum is a potential interfering factor for streptavidin-biotin-based assays. We aimed to evaluate the effective half-life of biotin and biotin metabolites, and establish a pharmacokinetic (PK) model to simulate the time taken for the biotin concentration to fall below a series of thresholds.Materials & methods: PK properties of biotin (5, 10 and 20 mg daily) were evaluated in healthy participants. Biotin serum concentrations were simulated for high-dose regimens (1 mg daily to 300 mg q.i.d.) using a population PK model.Results: Washout periods required for biotin concentrations to reach thresholds ranging from 10 to 100 ng/ml were successfully simulated.Conclusion: Our simulations provide valuable guidance on biotin washout periods necessary to avoid false assay results.